Quality Assurance, Monitoring, and Accreditation in Teacher Professional Education: A Conceptual Study of Relations, Challenges, and Development Directions - Muhammad Iqbal; Rila Hardiansyah; Ahmad Muslim; M. Rasyid Ridlo (Jurnal Diferensiasi: Jurnal Hasil Penelitian, Pengembangan dan Kajian Kepustakaan di Bidang Pendidikan, 2025)
Abstract: The Teacher Professional Education Program (Program Pendidikan Profesi Guru/PPG) is a strategic instrument within the national education system for producing competent professional teachers. In its implementation, PPG involves various quality mechanisms, including internal quality assurance, monitoring and evaluation (monev), and external accreditation. This conceptual study aims to analyze the position and function of these three quality mechanisms, identify areas of overlapping functions and instruments, and formulate directions for developing a more integrated PPG quality system. Using a critical analysis and theoretical synthesis approach on policy documents, regulations, and scientific literature, this study reveals substantial similarities in the indicators and assessed aspects across quality mechanisms, the dominance of a compliance-based approach oriented towards administrative completeness, and unclear role boundaries between mechanisms. This study also critiques the validity of evaluating the impact of the PPG program, given its relatively short duration (one year), which is theoretically inadequate for measuring substantial impact on teacher or prospective teacher performance. The implications of this study point to the need for a quality system integration oriented towards continuous improvement and outcome-based evaluation with long-term impact. Abstrak: Program Pendidikan Profesi Guru (PPG) merupakan instrumen strategis dalam sistem pendidikan nasional untuk menghasilkan guru profesional yang kompeten. Dalam penyelenggaraannya, PPG melibatkan berbagai mekanisme mutu yang meliputi penjaminan mutu internal, monitoring dan evaluasi (monev), serta akreditasi eksternal. Kajian konseptual ini bertujuan untuk menganalisis posisi dan fungsi ketiga mekanisme mutu tersebut, mengidentifikasi area tumpang tindih fungsi dan instrumen, serta merumuskan arah pengembangan sistem mutu PPG yang lebih terintegrasi. Dengan menggunakan pendekatan analisis kritis dan sintesis teoretik terhadap dokumen kebijakan, regulasi, dan literatur ilmiah, kajian ini mengungkap bahwa terdapat kesamaan substansial dalam indikator dan aspek yang dinilai antar mekanisme mutu, dominasi pendekatan compliance-based yang berorientasi pada kelengkapan administratif, serta ketidakjelasan batas peran antar mekanisme. Kajian ini juga mengkritisi validitas evaluasi dampak program PPG mengingat durasi program yang relatif singkat (satu tahun) yang secara teoretis tidak memadai untuk mengukur dampak substantif terhadap kinerja guru atau calon guru. Implikasi kajian ini mengarah pada kebutuhan integrasi sistem mutu yang berorientasi pada perbaikan berkelanjutan dan evaluasi berbasis outcome dan dampak jangka panjang.